New‐Onset Diabetes After Transplantation: Results From a Double‐Blind Early Corticosteroid Withdrawal Trial. Issue 7 (16th April 2015) - Pirsch, J. D.; Henning, A. K.; First, M. R.; Fitzsimmons, W.; Gaber, A. O.; Reisfield, R.; Shihab, F.; Woodle, E. S.
<x xml:space="preserve">Abstract</x> New‐onset diabetes after transplantation (NODAT) is an important complication following kidney transplantation. Data from the 5‐year early steroid withdrawal double‐blind randomized trial were analyzed to determine if steroid avoidance reduced the NODAT risk. Incidence, timing and risk factors for NODAT were evaluated using eight definitions. By American Diabetes Association definition, 36.3% of patients on chronic corticosteroids (CCS) and 35.9% on early corticosteroid withdrawal (CSWD) were diagnosed with NODAT by 5 years. The definition combining fasting blood glucose ≥126 mg/dL on two occasions or treatment identified slightly more cases of NODAT: CCS (39.3%) and CSWD (39.4%). Through 5 years posttransplant, the proportion of NODAT patients requiring treatment were similar (CSWD 22.5% vs. CCS 21.5%); however, insulin therapy was lower with CSWD (3.7% vs. 11.6%; p = 0.049). By multivariate analysis, only age, but not corticosteroid use, was a significant risk factor for NODAT for more than one definition. Numerical, but not statistically significant trends toward lower NODAT rates with CSWD were observed through 5 years for insulin use, HbA1c ≥6.0% and ≥6.5% on two occasions. This prospective, randomized trial of CSWD indicates that CSWD has a limited impact in reducing NODAT when compared to low‐dose prednisone (5 mg/day from month 6 to 5 years).